2019
DOI: 10.6061/clinics/2019/e771
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged response to recombinant human erythropoietin treatment in patients with myelodysplastic syndrome at a single referral centre in Brazil

Abstract: OBJECTIVES: To evaluate the effects of epoetin (EPO) alfa treatment on overall survival, event-free survival and response duration in patients with myelodysplastic syndrome (MDS) who were treated at a haematological referral centre in northeastern Brazil. METHODS: This was a retrospective cohort study of 36 patients diagnosed with MDS and treated with EPO alfa at 30,000 to 60,000 IU per week. Clinical data were collected from medical records. The events assessed were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…In this study, the treatment response rates at the 24-month, 36-month, and 48-month visits in the epoetin alfa (43.0%, 33.6%, and 27.1%) and darbepoetin alfa (29.9%, 22.7%, and 16.5%) groups were lower than the 12-month response rates in each group (44.9% and 46.4%, respectively). These findings are consistent with the overall response rates ranging from 20% to 40% and durations of response ranging from 10 to 24 months reported in previous studies on ESAs, considering the refractoriness rate for ESAs to be approximately 40%-50% after 2 years of treatment [ 6 , 10 , 11 ]. Specifically, multicenter studies of epoetin-treated patients with MDS revealed response rates of approximately 30%-50% with durations of 12-24 months [ 1 , 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], while single-arm darbepoetin alfa studies reported durations of response ranging from 1 to 36 months [ 17 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the treatment response rates at the 24-month, 36-month, and 48-month visits in the epoetin alfa (43.0%, 33.6%, and 27.1%) and darbepoetin alfa (29.9%, 22.7%, and 16.5%) groups were lower than the 12-month response rates in each group (44.9% and 46.4%, respectively). These findings are consistent with the overall response rates ranging from 20% to 40% and durations of response ranging from 10 to 24 months reported in previous studies on ESAs, considering the refractoriness rate for ESAs to be approximately 40%-50% after 2 years of treatment [ 6 , 10 , 11 ]. Specifically, multicenter studies of epoetin-treated patients with MDS revealed response rates of approximately 30%-50% with durations of 12-24 months [ 1 , 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], while single-arm darbepoetin alfa studies reported durations of response ranging from 1 to 36 months [ 17 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the increased likelihood of transfusion independency with long-term epoetin treatment and lower-risk MDS in our cohort seems to be particularly notable given that the primary target in managing patients with lower-risk MDS in daily practice is to achieve transfusion independence, which is associated with improved survival [ 6 , 15 , 20 , 33 , 34 , 35 ]. Indeed, epoetin alfa treatment for patients with MDS is considered likely to achieve durable responses, thereby guaranteeing an improvement in the quality of life for these patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations